Meningkatan Kemampuan Berpikir Kritis Dan Kreatif Siswa Pembelajaran Matematika Menggunakan Model PUZZLE Di Kelas V - M. Faisal; Aslamiah (CV. ITTC INDONESIA, 2023)
The problem in this study is the low ability to think critically and think creatively of students, this arises because the learning carried out has not contained critical thinking activities and there are no opportunities for students to be creative. The effort to solve this problem is by using the PUZZLE model (Problem Based Learning, Snowball Throwing, Numbered Head Together). This study aims to describe teacher activities and analyze students' critical and creative thinking skills. The type of research carried out is classroom action research (PTK) with a qualitative approach. The research setting is SDN Kelayan Selatan 3 Banjarmasin. The research instruments used are observation sheets for teacher activities, critical thinking, and creative thinking and evaluation sheets for written tests. As for data analysis, descriptive and cross-table analysis is used and interpretation uses percentages and criteria. The findings at meeting 3 showed that teacher activities had been carried out